Impact of the reformulation of the National Primary Care Policy on the work process of Community Health Agents in a municipality in south of Brazil (Research, Society and Development, 2020)
The publication of the National Policy for Primary Care (PNAB) 2017 brought changes in relation to the performance of Community Health Agents (ACS), coupled with this there is also a difficulty in establishing processes evaluated to the work of this professional. This research aims to evaluate the work process of CHWs in the municipality of Araranguá/SC, enabling a comparison of the scenario before and after the publication of the 2017 PNAB. Data were collected through structured information in the 15 Basic Health Units (UBS), being carried out in three phases. The first addressed to the knowledge of the ACS, the second directed to two residents of different residences and, finally, the questionnaire for an employee where the ACS works. 19 CHA were interviewed when PNAB 2011 was still in force and 14 CHA after the publication of PNAB in 2017. There were no significant differences in the comparison of issues related to the CHA's work process. However, in matters related to home visits, we observed a decrease with the new term, in addition, we noticed a greater knowledge about the risk areas belonging to the agent's area of activity. The evidenced results are obliged to fulfill that the changes of the PNAB 2017 directly interfered in the performance of the CHA. Although the research was carried out precisely in the transition period in the update of the PNAB implemented in 2017, it is clear the impact in the scope of assistance coverage, especially in relation to the object of the work of the CHA.